Pro-Drop in Hijazi Arabic: A Minimalist Perspective - AlQurashi, Issa (European Scientific Journal, ESJ, 2023)
The purpose of this paper is to investigate the null subjects in Hijazi Arabic and address how they are derived and interpreted. There is a strong connection between rich verbal agreement inflection and pro-drop in HA as it is a highly inflectional language. It is shown in this paper that HA is a consistent null subject language. This study is framed within Holmberg’s (2005, 2010) theory of null subjects. Holmberg proposed that null subjects (henceforth NSs) are defective subject pronouns labeled φPs. The null subjects are derived via incorporation into T after the features valuation and union take place. The head T (a probe) has unvalued ϕ-features which are valued by the defective subject pronoun (a goal) and in return, the [u case] feature on φP is valued by T. The incorporation of φP into T forms a chain which is subject to chain reduction where the lower chain copy (the defective subject pronoun in spec-VP) receives a null spell out. what is pronounced is the valued ϕ-features of T which appears as a verbal affix on the finite verb after the verb also gets incorporated in T. This reflects the deletion of the subject in spec-VP. The null subject is interpreted as a definite 3rd person null subject when the [uD(efiniteness)] feature of φP is valued by an A-Topic (antecedent) in spec-TopP. On the other hand, it is interpreted as a definite 1st or 2nd person null subject if it is valued by speaker/addressee features in the domain of C (Complementizer).